Bài 1 : Tính a) x^2 . ( x – 2x^3 ) b) -4x^3 . ( 3x^2 + 2x – 5 ) c) 6x^2y . ( 3x – 2y^2x + y ) d) ( 4x^2 + 5x – 1 ) . ( 2x

Bài 1 : Tính
a) x^2 . ( x – 2x^3 )
b) -4x^3 . ( 3x^2 + 2x – 5 )
c) 6x^2y . ( 3x – 2y^2x + y )
d) ( 4x^2 + 5x – 1 ) . ( 2x^3 – 3x )

2 bình luận về “Bài 1 : Tính a) x^2 . ( x – 2x^3 ) b) -4x^3 . ( 3x^2 + 2x – 5 ) c) 6x^2y . ( 3x – 2y^2x + y ) d) ( 4x^2 + 5x – 1 ) . ( 2x”

  1. Giải đáp:
    a)
    x^{2}.(x-2x^{3})
    =x^{2}.x-x^{2}.2x^{3}
    =x^{3}-2x^{5}
    =-2x^{5}+x^{3}
    b)
    -4x^{3}.(3x^{2}+2x-5)
    =(-4x^{3}).3x^{2}+(-4x^{3}).2x+(-4x^{3}).(-5)
    =-12x^{5}-8x^{4}+20x^{3}
    c)
    6x^{2}y.(3x-2y^{2}x+y)
    =6x^{2}y.3x-6x^{2}y.2y^{2}x+6x^{2}y.y
    =18x^{3}y-12x^{3}y^{3}+6x^{2}y^{2}
    d)
    (4x^{2}+5x-1).(2x^{3}-3x)
    =4x^{2}.(2x^{3}-3x)+5x.(2x^{3}-3x)-1.(2x^{3}-3x)
    =8x^{5}-12x^{3}+10x^{4}-15x^{2}-2x^{3}+3x
    =8x^{5}+10x^{4}-(12x^{3}+2x^{2})-15x^{2}+3x
    =8x^{5}+10x^{4}-14x^{3}-15x^{2}+3x

    Trả lời

Viết một bình luận

Câu hỏi mới